Assessment of Pradhana Sharir and Manas Prakriti(bodily and mental constitution) in the manifestation of diabetes mellitus - Amin Hetalben; Hitesh Vyas; Mahesh Vyas (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: Diabetes mellitus (DM) is the most menacing disorder in Ayurveda, and it is equated to Madhumeha. The concept of Prakriti (human constitution) can be applied for manifestation and prognosis of diseases. Therefore, in this study, we intend to study Pradhana Sharira and Manas Prakriti (dominant bodily and mental constitution) in Madhumeha (DM)) participants. Materials and Methods: Prakriti of 103 participants of DM was assessed as per Prakriti assessment pro forma. Vata-, Pitta-, and Kapha Dosha (bodily humors)-dominant Prakriti were analyzed according to the characteristics found in participants. Results: Nearly 38.46% Kapha Pradhana Prakriti and 41.5% Tamas Pradhana Prakriti participants were found maximum. Conclusion: Dominant Kapha and Tamas Prakriti have influence on the manifestation of Madhumeha (DM).